1998
DOI: 10.1063/1.120907
|View full text |Cite
|
Sign up to set email alerts
|

Study of Cu gettering to cavities in separation by implantation of oxygen substrates

Abstract: Gettering of Cu impurities to cavities induced in separation by implantation of oxygen (SIMOX) substrates has been investigated. The cavities were introduced beneath the buried oxide layer (BOX) of SIMOX by H+ implantation and subsequently annealing. 5×1013/cm2 or 5×1015/cm2 of Cu impurities were implanted in the top Si layer. The results indicate that the BOX layer does not appear to prevent the movement of Cu at temperatures higher than 700 °C. Profiles of Cu indicate that 92% of the initial 5×1013/cm2 Cu ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…However, our previous work has demonstrated that Cu precipitate indeed form in the cavities when the amount of trapped Cu exceeds the number of trapping sites. 24 Comparing the bulk Si with SIMOX after 700°C annealing, the amount of Cu trapped in the microcavity band in SIMOX is much less than that in bulk Si. This is due to the gettering of the intrinsic defects at the BOX interfaces in SIMOX.…”
Section: Resultsmentioning
confidence: 99%
“…However, our previous work has demonstrated that Cu precipitate indeed form in the cavities when the amount of trapped Cu exceeds the number of trapping sites. 24 Comparing the bulk Si with SIMOX after 700°C annealing, the amount of Cu trapped in the microcavity band in SIMOX is much less than that in bulk Si. This is due to the gettering of the intrinsic defects at the BOX interfaces in SIMOX.…”
Section: Resultsmentioning
confidence: 99%
“…The accumulation of indium atoms at the BOX-Si interfacial region can be attributed to the indium segregation into this region possessing a substantially lower stoichiometry and effective damage and the dangling Si bonds in SiO x similar to the behavior of some metal atoms in this BOX region in the SIMOX as reported before. 27 Furthermore, the high-density oxygen vacancies in the BOX layer are also expected to play an important role in the diffusion of indium atoms from the top Si-BOX interface into the underlying BOX layer. It is found that the oxygen-vacancy defect (E' center) generation sensitivity is fairly constant throughout the entire BOX layer with a pronounced decline toward the BOX-substrate interface.…”
Section: Resultsmentioning
confidence: 99%
“…The SOI R&D is pioneered and undertaken by Professor Lin Chenglu and coworkers including Professor Zhang Miao and Liu Weili at Shanghai Institute of Microsystem and information Technology, Chinese Academic of Sciences (SIMIT, CAS) [2,3] .…”
Section: Introductionmentioning
confidence: 99%